2017
DOI: 10.1037/adb0000295
|View full text |Cite
|
Sign up to set email alerts
|

Between- and within-person associations between negative life events and alcohol outcomes in adolescents with ADHD.

Abstract: Escalations in alcohol use during adolescence may be linked with exposure to negative life events, but most of this research has focused on between person associations. Moreover, adolescents with ADHD may be an especially vulnerable population, reporting more life events, alcohol involvement, and may even be more sensitive to the effects of life events on alcohol outcomes compared to those without ADHD. We tested the between and within person effects of the number and perceptions of negative life events on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 70 publications
(110 reference statements)
1
13
0
Order By: Relevance
“…Thus, experiencing additional stressful life events that are due to heavy drinking, which is a well-established phenomenon (Brennan et al 1999;Hart and Fazaa 2004), may be particularly problematic for adults with an ADHD history. Moreover, those with ADHD may perceive negative life events, such as those emanating from heavy drinking, more negatively than individuals without ADHD (King et al 2017). Because individuals who perceive life events more negatively have been shown to be at risk for depression (Kuiper et al 1986), individuals with ADHD may be particularly prone to becoming depressed as a result of negative drinking-related life events.…”
Section: Adhd Heavy Alcohol Use and Depressive Symptomsmentioning
confidence: 99%
“…Thus, experiencing additional stressful life events that are due to heavy drinking, which is a well-established phenomenon (Brennan et al 1999;Hart and Fazaa 2004), may be particularly problematic for adults with an ADHD history. Moreover, those with ADHD may perceive negative life events, such as those emanating from heavy drinking, more negatively than individuals without ADHD (King et al 2017). Because individuals who perceive life events more negatively have been shown to be at risk for depression (Kuiper et al 1986), individuals with ADHD may be particularly prone to becoming depressed as a result of negative drinking-related life events.…”
Section: Adhd Heavy Alcohol Use and Depressive Symptomsmentioning
confidence: 99%
“…Socioeconomic indicators controlled for at each wave include enrollment in school (1 = yes, 0 = no), respondent education (high school or less, some college, college degree), and whether respondents work 35 or more hours per week (1 = yes, 0 = no). Binge drinking and cigarette smoking are also controlled for, given research showing that both are significantly associated with depressive symptoms, ADHD, and family transitions (Faraone et al 2007; King et al 2017). Binge drinking is an ordinal indicator summarizing how often over the past year respondents consumed five or more alcoholic beverages in one sitting (ranging from 0 [no binge drinking] to 6 [binge drinking daily or nearly every day]).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in adulthood ADHD-related symptoms are associated with making riskier decisions (Matthies, Philipsen, and Svaldi 2012), more regret over past decisions (Schepman et al 2012), and more harmful coping strategies such as avoidance or detachment to manage problems (Young 2005). These behavioral impairments are broadly implicated in associations of ADHD in adulthood with a higher risk for suicide (Biederman et al 2008; Ljung et al 2014), more substance use (Faraone et al 2007; King, Boyd, and Thorsen 2017), poorer employment outcomes (Fletcher 2014), lower educational attainment and income (Barkley et al 2006; Biederman et al 2006), and more criminal activity (Fletcher and Wolfe 2009). In addition, ADHD is associated with a greater total number of negative life events, even after controlling for the effects of comorbid mental health issues (Garcia et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…After review, 49 articles were included based on their significance to ADHD and its association with alcohol abuse. Table 1 lists various studies indicating an interdependence between the risk of alcohol use and ADHD patients [4,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Several studies have reported that ADHD and alcohol abuse have a direct positive correlation [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Reviewmentioning
confidence: 99%